Riluzole: Anti-Invasive Effects on Rat Prostate Cancer Cells Under Normoxic and Hypoxic Conditions - Rizaner, Nahit; Uzun, Sercan; Fraser, Scott P.; Djamgoz, Mustafa B. A.; ALTUN, SEYHAN (Blackwell Publishing Ltd., 2020)
Anti-invasive effects of riluzole and ranolazine, a neuro-protectant and an anti-anginal drug, respectively, on Mat-LyLu rat prostate cancer (PCa) cells were tested in vitro (a) at non-toxic doses and (b) under both normoxic and hypoxic conditions, the latter common to growing tumours. Tetrodotoxin (TTX) was used as a positive control. Hypoxia had no effect on cell viability but reduced growth at 48 hours. Riluzole (5 μmol/L) or ranolazine (20 μmol/L) had no effect on cell viability or growth under normoxia or hypoxia over 24 hours. Matrigel invasion was not affected by hypoxia but inhibited by TTX, ranolazine and riluzole under a range of conditions. The expression of Nav1.7 mRNA, the prevailing, pro-invasive voltage-gated sodium channel α-subunit (VGSCα), was up-regulated by hypoxia. Riluzole had no effect on Nav1.7 mRNA expression in normoxia but significantly reduced it in hypoxia. VGSCα protein expression in plasma membrane was reduced in hypoxia; riluzole increased it but only under hypoxia. It was concluded (a) that riluzole and ranolazine have anti-invasive effects on rat PCa cells and (b) that Nav1.7 mRNA and protein expression can be modulated by riluzole under hypoxia. Overall, therefore, riluzole and ranolazine may ultimately be "repurposed" as anti-metastatic drugs against PCa.
Keywords: Hypoxia; Invasion; Prostate Cancer; Riluzole; Voltage-Gated Sodium Channel